To match the equations on the left with their equivalents on the right, we can simplify and manipulate each equation from the left side and see which right side form corresponds.
-
Left side: \(y = x^2 - 1x - 20\)
- Factor:
\(y = x^2 - x - 20 = (x - 5)(x + 4)\) - Match: \(y = (x + 4)(x - 5)\) (This is from the right side)
- Factor:
-
Left side: \(y = (x + 4)^2 - 5\)
- Expand:
\(y = (x^2 + 8x + 16) - 5 = x^2 + 8x + 11\) - Match: \(y = x^2 + 8x + 11\) (This is from the right side)
- Expand:
-
Left side: \(y = x^2 - 6x + 16\)
- Completing the square:
\(y = (x^2 - 6x + 9) + 7 = (x - 3)^2 + 7\) - Match: \(y = (x - 3)^2 + 7\) (This is from the right side)
- Completing the square:
-
Left side: \(y = x^2 + 19x + 88\)
- This does not appear directly on the left side but implies some part of \(y = (x + 8)(x + 11)\) when set to zero. If we expand the right side:
\((x + 8)(x + 11) = x^2 + 19x + 88\) - Match: \(y = (x + 8)(x + 11)\)
- This does not appear directly on the left side but implies some part of \(y = (x + 8)(x + 11)\) when set to zero. If we expand the right side:
So the final matches are:
- \(y = x^2 - 1x - 20 \) ⇔ \(y = (x + 4)(x - 5)\)
- \(y = (x + 4)^2 - 5\) ⇔ \(y = x^2 + 8x + 11\)
- \(y = x^2 - 6x + 16\) ⇔ \(y = (x - 3)^2 + 7\)
- \(y = (x + 8)(x + 11)\) ⇔ \(y = x^2 + 19x + 88\)
The complete matched pairs are:
- \(y = x^2 - 1x - 20 \) ↔ \(y = (x + 4)(x - 5)\)
- \(y = (x + 4)^2 - 5\) ↔ \(y = x^2 + 8x + 11\)
- \(y = x^2 - 6x + 16\) ↔ \(y = (x - 3)^2 + 7\)
- \(y = (x + 8)(x + 11)\) ↔ \(y = x^2 + 19x + 88\)